1999
DOI: 10.1002/(sici)1099-1654(199907/09)9:3<147::aid-rmv255>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

The selectivity of action of an antiherpetic agent, 9-(2-hydroxyethoxymethyl) guanine

Abstract: Nachhaltigkeit ist zugleich historisches Kulturgut und moderne Antwort auf die aktuelle globale Krisensituation im Kontext des Klimawandels. Insbesondere im Bauwesen ist der strategische Ansatz der Nachhaltigkeit in den letzten Jahren durch die Entwicklung und Implementierung von Nachhaltigkeitszertifizierungssystemen fest verankert worden. Derzeit weist die Bau‐ und Immobilienwirtschaft vor allem in den Bereichen der Diversifikation entwickelter Bewertungs‐ und Optimierungswerkzeuge und der Ausbildung eines p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
163
0
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(167 citation statements)
references
References 13 publications
1
163
0
3
Order By: Relevance
“…6 It was reported that, once GCV entered the cells, it is readily phosphorylated by HSVtk, losing its ability to pass through cell membranes. 25,26 Thus, its half-life within the cell is about six-fold longer than that of unmodified GCV. 25,26 Preliminary data of Hematoxylin and eosin staining of 5-day-old LM05e, LM3 and B16 multicellular spheroids sections.…”
Section: Spheroids Displayed a High Fraction Of Quiescent Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 It was reported that, once GCV entered the cells, it is readily phosphorylated by HSVtk, losing its ability to pass through cell membranes. 25,26 Thus, its half-life within the cell is about six-fold longer than that of unmodified GCV. 25,26 Preliminary data of Hematoxylin and eosin staining of 5-day-old LM05e, LM3 and B16 multicellular spheroids sections.…”
Section: Spheroids Displayed a High Fraction Of Quiescent Cellsmentioning
confidence: 99%
“…25,26 Thus, its half-life within the cell is about six-fold longer than that of unmodified GCV. 25,26 Preliminary data of Hematoxylin and eosin staining of 5-day-old LM05e, LM3 and B16 multicellular spheroids sections. Spheroids were collected, embedded in paraffin and cross-sections were stained for BrdU or hematoxylin and eosin as indicated in Materials and methods.…”
Section: Spheroids Displayed a High Fraction Of Quiescent Cellsmentioning
confidence: 99%
“…One of the most important characteristics of retrovirus is their preferential infection of the dividing cells, hence, the tumor has been primarily considered as a target of retroviralmediated gene therapy. Similar vectors carrying HSV-tk have been described in recent report for treatment of melanoma [14], lymphoma [15] and glioma cells [5].…”
Section: Discussionmentioning
confidence: 93%
“…The supernatant of the transfected cells (PA317-lacZ), with titer consistent to that of PA317tk (1 10 6 cfu/ml), was used to infect BEL-7402 and followed by X-gal staining (Fig 1). Since the essential titer of retrovirus for efficient delivery of gene to target cells was 5 10 5 cfu/ml [12], this titer of 1 10 6 cfu/ml was theoretically adequate to produce satisfied gene transfers. It was obviously seen in Southern blot that a 3.4 kb band was generated when hybridizing genomic DNA of PA317tk and BEL-7402tk with HSV-tk BamH I fragment (Fig 2a).…”
Section: Efficiency Of Gene Transfer and Expression Of Tk Genementioning
confidence: 99%
See 1 more Smart Citation